2014
DOI: 10.1377/hlthaff.2013.0832
|View full text |Cite
|
Sign up to set email alerts
|

Switching To Less Expensive Blindness Drug Could Save Medicare Part B $18 Billion Over A Ten-Year Period

Abstract: The biologic drugs bevacizumab and ranibizumab have revolutionized treatment of diabetic macular edema and macular degeneration, leading causes of blindness. Ophthalmologic use of these drugs has increased, now accounting for roughly one-sixth of the Medicare Part B drug budget. Ranibizumab and bevacizumab have similar efficacy and potentially minor differences in adverse event rates, but at $2,023 per dose, ranibizumab costs forty times more than bevacizumab. Using modeling methods, we predict ten-year (2010–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 34 publications
1
55
0
2
Order By: Relevance
“…The lower cost of bevacizumab, perceived effectiveness and relative safety make it a popular choice particularly in low-income and middle-income countries 4 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower cost of bevacizumab, perceived effectiveness and relative safety make it a popular choice particularly in low-income and middle-income countries 4 5…”
Section: Discussionmentioning
confidence: 99%
“…However, intravitreal bevacizumab (IVB) has been widely used off-label despite approved therapies. The lower cost of bevacizumab, perceived effectiveness and relative safety makes it a popular choice particularly in the developing world 4 5. Numerous reports have presented beneficial visual and anatomical results 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Aflibercept (Eylea; Bayer/Regeneron, Tarrytown, NY) is a more recent anti-VEGF therapeutic with a higher affinity for VEGF, and its use in clinical trials has demonstrated noninferiority in visual outcomes to monthly ranibizumab injections, despite only being injected every 2 months after the first loading dose phase. 4 As well as ranibizumab and aflibercept, many ophthalmologists globally use bevacizumab (Avastin, Genentech) off-label, which is a less-expensive anti-VEGF alternative 5 and has demonstrated noninferiority of visual outcomes compared with ranibizumab in large, randomized controlled trials. 6e9 Delivery regimens for each of these agents varies; treatment by monthly injections has been used as a gold standard strategy for visual outcomes in comparison trials, but is rarely followed in clinical practice, with most physicians opting for less frequent injection regimens using as-needed treatments, or regimens whereby treatment intervals are varied according to disease activity.…”
mentioning
confidence: 99%
“…Both ranibizumab monotherapy and in combination with laser resulted in gain in quality-adjusted life-years [66]. However, the increased quality achieved by the FDA-approved anti-VEGF agents comes at a high cost: US$1247 per one dose of 0.3 mg ranibizumab and $1970 per one dose of 2.0 mg aflibercept [67][68][69]. In comparison to ranibizumab and aflibercept, one injection of bevacizumab costs approximately US$50 [70].…”
Section: Cost-effectivenessmentioning
confidence: 99%